2012
DOI: 10.1007/978-3-642-30439-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Adopting Agile Practices When Developing Medical Device Software

Abstract: Agile methodologies such as XP and Scrum are founded upon the four values and twelve principles of agile software development. A software development project is only considered to be truly agile if these values and principles are followed. However, software developed for use in medical devices must be regulatory compliant and this can make the process of following a single agile methodology such as XP difficult to achieve. This paper outlines how we identified the barriers to agile adoption in the medical devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 8 publications
0
39
0
Order By: Relevance
“…For example, Pair Programming and TDD worked well for Medtronic providing them early feedback and improved quality [23]. A survey of 20 Irish MD software development organisations in 2012 revealed that 50 % of organisations were using the V-Model, 25 % of them were following an agile approach and the "remaining 25 % used other development lifecycles such as the Waterfall, and Iterative & Incremental approaches" [25]. The case studies [9,16,23,26] highlighted that following an agile approach "can resolve problems associated with plan driven software development" [25].…”
Section: Use Of Agile In Highly Regulated Environmentsmentioning
confidence: 98%
“…For example, Pair Programming and TDD worked well for Medtronic providing them early feedback and improved quality [23]. A survey of 20 Irish MD software development organisations in 2012 revealed that 50 % of organisations were using the V-Model, 25 % of them were following an agile approach and the "remaining 25 % used other development lifecycles such as the Waterfall, and Iterative & Incremental approaches" [25]. The case studies [9,16,23,26] highlighted that following an agile approach "can resolve problems associated with plan driven software development" [25].…”
Section: Use Of Agile In Highly Regulated Environmentsmentioning
confidence: 98%
“…McHugh et al [9] address flexibility from a process perspective, basing their work on an industrial survey, in which they investigated barriers preventing the adoption of agile practices in safety-critical medical device development. They found that the barriers they identified were tightly coupled with current regulatory constraints on medical software, but they emphasized that the barriers were not insurmountable even with todays best practices and standards.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Therefore, eXtreme Programming can be used in conjunction with Scrum . Case studies have emphasized that following an agile approach can overcome the issues associated with plan‐driven software development …”
Section: Approach Used To Understand the Needs For Mma Development Frmentioning
confidence: 99%
“…2 Case studies 35,[39][40][41] have emphasized that following an agile approach can overcome the issues associated with plan-driven software development. 42 Participants felt that by integrating agile practices into the V-model development life cycle, it provides the advantage of accommodating changes more easily than the previous 2 approaches.…”
Section: Introducing Agile Practices Into the V-model Life Cycle (Nmentioning
confidence: 99%